Awareness and perception of Agile in saudi software industry - Altuwaijri, Fahad S; Ferrario, Maria Angela (2021 IEEE/ACM 43rd International Conference on Software Engineering: Software Engineering in Society (ICSE-SEIS), 2021)
Over the last two decades, Agile software development methodology has garnered significant interest in both software industry and research with several studies investigating the level of awareness, perception and use of Agile in software engineering practice. However, most of these studies have focused on Agile practice in developed countries, with only a handful having been conducted in developing countries, especially in the Middle East. This is problematic given the strategic and economic importance of software industry in countries such as Saudi Arabia. This paper aims to start addressing this research gap with an empirical investigation of the awareness and perceptions of Agile among software practitioners in Saudi Arabia and the extent to which they are adopting Agile methods. To this end, we conduct four semi-structured interviews with expert software practitioners and a survey with 31 respondents, all from the mobile development software industry. Our findings indicate that there it seems to be a low level of awareness and usage of Agile in the country. However, we also find that those who use Agile, are appreciative of its benefits which include project management flexibility, rapid response to change, and a positive effect on team morale and communication.